An Optically Pure Apogossypolone Derivative as Potent Pan-Active Inhibitor of Anti-Apoptotic Bcl-2 Family Proteins - Wei, Jun; Stebbins, John L.; Kitada, Shinichi; Dash, Rupesh; Zhai, Dayong; Placzek, William J.; Wu, Bainan; Rega, Michele F.; Zhang, Ziming; Barile, Elisa; Yang, Li; Dahl, Russell; et al. (Frontiers in Oncology, 2011)
Our focus in the past several years has been on the identification of novel and effective pan-Bcl-2 antagonists. We have recently reported a series of Apogossypolone (ApoG2) derivatives, resulting in the chiral compound (+/-) BI97D6. We report here the synthesis and evaluation on its optically pure (-) and (+) atropisomers. Compound (-) BI97D6 potently inhibits the binding of BH3 peptides to Bcl-XL, Bcl-2, Mcl-1 and Bfl-1 with IC50 values of 76 ± 5, 31 ± 2, 25 ± 8 and 122 ± 28 nM, respectively. In a cellular assay, compound (-) BI97D6 effectively inhibits cell growth in the PC-3 human prostate cancer and H23 human lung cancer cell lines with EC50 values of 0.22 ± 0.08 and 0.14 ± 0.02 µM, respectively. Similarly, compound (-) BI97D6 effectively induces apoptosis in the BP3 human lymphoma cell line in a dose-dependent manner. The compound also shows little cytotoxicity against bax-/-/bak-/- cells, suggesting that it kills cancers cells predominantly via a Bcl-2 pathway. Moreover, compound (-) BI97D6 displays in vivo efficacy in both a Bcl-2 transgenic mouse model and in a prostate cancer xenograft model in mice. Therefore, compound (-) BI97D6 represents a promising drug lead for the development of novel apoptosis-based therapies for cancer.